Does Interactivity in an English Presentation Affect its Preparation Process? - Fumiya Shinozaki; Hiroaki Aoki (Universitas Islam Negeri Walisongo Semarang, 2023)
The purpose of this study is to clarify the differences in the process of students’ preparation and practice outside of class for a one-way or interactive English presentation. The participants were 105 third-year junior high school students in Japan. They were supposed to record their actions while preparing for each type of presentation outside of class for a week. A hierarchical cluster analysis was conducted on all learners based on a self-evaluation questionnaire administered beforehand. Three clusters were created from the dendrogram. Kruskal-Wallis test and multiple comparisons showed significant differences among all items. Each cluster was named